Distributions of the Number of Claims in Motor Liability Car Insurance - Szymańska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Determining the amount of the insurance premium is the primary task of each insurance company. In motor liability car insurance determining of premiums requires the knowledge of distribution of the number and amount of claims in the portfolio. The paper presents the most commonly used in motor insurance distributions modeling the number of claims and highlights the methodological problems to evaluate the fit of empirical data to theoretical distributions.